Forced And Early Marriages: Moral Failures Vs Religious Nuances - Itebiye, Bernard O. (European Scientific Journal, ESJ, 2016)
The rights of the child all over the world are considered to be very important. But forces and early marriages have become some of the ways the rights of children are being abused. This paper aimed at shedding more light on why children are victims of forced and early marriages and the effects and consequences of such marriages on the child and the society. The analyses employed Critical Discourse Analysis (CDA) framework. Data gathered both from the primary and secondary sources were analyzed through the hermeneutical, descriptive and analytical methods. The findings of this paper are that early and forced marriages have harmful developmental, psychological and physical consequences on the child; have negative effects on the society and the Nation at large; that scriptural assertions, in defense, are mere manipulative ideas to cover up moral failures; and that whatever reason is given for child marriage, the disastrous effects on the victims outweigh them and undoubtedly make child marriage a social evil. The paper concludes that early and forced marriages do exist in Nigeria and needs to be curbed and thereafter suggests strategies that will make for a better implementation of such laws to effectively curb forced and early marriages in Nigeria.